Thermal Regime of Earth Rock Dams Constructed in the Far North (Termicheskii Regim Kamenno-Zemlynkh Plotin Vozvodimkh ma Krainem Severe) - Plyat,Sh N; Mukhetdinov,N A (1977)
This report describes methods developed at VNIIG to calculate the thermal regime of earth dams, along with data from field observations of such structures. (Author) Trans. of Soviet-American working seminar 'Technology of Construction of Structures under Cold Climate Conditions', Leningrad (USSR) 25-26 May 77, 14p 1977.